Superior vena cava syndrome after creation of arteriovenous fistula - Akgul, Engin; Erkul, Sinan; Alptekin Erkul, Gulen Sezer; Vural, Ahmet Hakan (The European Research Journal, 2017)
Patients with end-stage renal disease require vascular access for hemodialysis. Repeated insertions and long-term duration of permanent central venous catheters may cause venous stenosis and thrombosis in central veins, which may result in superior vena cava syndrome. A 38-year-old male patient with end-stage renal disease was admitted with complaint of dyspnea, edema of the face, neck and bilateral upper extremities. We had created a radiocephalic arteriovenous fistula at the level of left wrist two weeks ago, he had a permanent catheter in the right internal jugular vein for 2 months. The Doppler ultrasound and venographic examinations of central veins showed that the permanent catheter in the right internal jugular vein had caused the edema of the neck, face and bilateral upper extremities by narrowing the superior vena cava. The catheter was removed and the patient was anticoagulated. The patient's symptoms of shortness of breath were alleviated on hospital discharge and the swelling of the upper extremities diminished after one week. The hemodialysis patients should be directed to arteriovenous fistula surgery instead of central venous catheterization as soon as possible to avoid superior vena cava syndrome due to central venous catheters.